Problems With Digital Currency: Cryptocurrency In Indonesia - Riadi Setia; Maria Maharani (Journal of Economics and Business UBS, 2023)
This study aims to analyze the Indonesian government's policies regarding cryptocurrency transactions and taxation and accounting practices in Indonesia. In addition, this research also conducts literature studies abroad. Commodity Futures Trading Regulatory Agency Regulation No. 13 of 2022 and No. 8 of 2021 concern guidelines for organizing crypto asset physical market trading on futures exchanges to oversee cryptocurrency transactions. Cryptocurrency transactions in Indonesia are considered VAT objects and are subject to income tax. Accountants face a challenge because there is no accounting standard that explains why cryptocurrency must be considered. It is hoped that the Indonesian Accounting Standards Board can conduct discussions related to accounting standards for cryptocurrency. Besides, the government's role is very important in making financial technology policies and systems in order to mitigate the risks of cryptocurrency transactions so that they can benefit investors and the tax system in Indonesia.